RANCANG BANGUN ALAT PAKAN IKAN OTOMATIS MENGGUNAKAN MIKROKONTROLER ESP8266 DENGAN BERBASIS INTERNET OF THINGS - Rofhan Zahma Anzary; Dian Ade Kurnia; Odi Nurdiawan (P3M Politeknik Negeri Indramayu, 2024)
Fish farming in general is a cultivation that is in great demand by Indonesian people. Discussing actions that can facilitate the maintenance of fish cultivators, for now fish feed is still mostly done directly by fish owners. Late feeding can affect the pond ecosystem, the appearance of cannibalism in fish and abnormal fish weight. The application of IoT technology is expected to make it easier for fish farmers, especially for pond areas and ponds, to provide feed when outside the city. The technology that will be applied is an automatic fish feeder that can be adjusted according to the fish feeding schedule automatically and can also monitor feed conditions through the Blynk application on a smartphone. The electronic components used are the ESP8266 as a data processor, the MG996R Servo Motor as the feed tap driver, the SG90 Servo Motor as the Potentiometer drive, the Potentiometer as the active control of the Blower, the Blower as the spreader of fish feed, the Ultrasonic Sensor HY-SRF05 as monitoring of feed conditions, the Power Supply as 12 V voltage input, Buzzer as an alarm notification and the Blynk application on a smartphone. The test results show that the built tool can function properly, setting the feed schedule and monitoring the feed runs normally according to the instructions set in the Blynk application.